Management of urological trauma associated with pelvic fractures. (2nd January 2021) - Trockels, Amaury; Ahluwalia, Aashish K; Chetwood, Andrew
Abstract : Urological trauma is frequently encountered in patients with high energy pelvic fractures and can have debilitating long-term sequelae for patients without appropriate multidisciplinary management. Anterior pelvic ring disruption causes a high incidence of bladder rupture and urethral injuries, and initial assessment requires urological tract imaging and emergent bladder drainage before subsequent surgical repair. Pelvic ring disruption requires urgent fixation and should be managed as an open fracture in the context of significant bladder and urethral injury with urinary leakage. Long-term outcomes are variable and genitourinary dysfunction is commonly reported among patients with pelvic fractures. Optimisation of patient outcomes relies heavily on collaborative management between orthopaedic and urological specialists and requires an appreciation of the anatomical intricacies of the pelvis. This article provides an overview of the British Orthopaedic Association Standards for Trauma and Orthopaedics management of urological trauma in the context of pelvic fractures.